Ostatni rok życia Polaków w świetle danych SHARE: analiza porównawcza - Kalbarczyk-Stęclik, Małgorzata; Nicińska, Anna (Studia Demograficzne, 2013)
The paper aims at describing the last year of life of Polish people in comparison with previous years of their life. We include international context as well as gender differences in the analysis. A descriptive part of the paper is based on data from end-of-life interviews of the Survey of Health, Ageing and Retirement in Europe (SHARE). The second part – comparative analysis – in addition to the end-of-life interviews takes into account regular interviews conducted in previous waves. We find differences in the process of health deterioration in the last year of life by cause of death. In particular, individuals who died due to cancer were often relatively healthy in the preceding years of life, but experienced a dramatic decrease in health during the last year of life. Another finding is that time spent in the hospital significantly increases in the last year of life. Moreover, we find that number of daily activities’ limitations is positively associated with care received in the last year of life. The results show that the last year of life is often significantly different than preceding years of life both in Poland and other European countries.